ELF.01.6 - Laws of Logarithms

1 / 12

# ELF.01.6 - Laws of Logarithms - PowerPoint PPT Presentation

ELF.01.6 - Laws of Logarithms. MCB4U - Santowski. (A) Review. if f(x) = a x , find f -1 (x) so y = a x then x = a y and now isolate y in order to isolate the y term, the logarithmic notation or symbol or function was invented or created so we write x = a y as y = log a (x).

I am the owner, or an agent authorized to act on behalf of the owner, of the copyrighted work described.

## PowerPoint Slideshow about 'ELF.01.6 - Laws of Logarithms' - linus-levy

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript

### ELF.01.6 - Laws of Logarithms

MCB4U - Santowski

(A) Review
• if f(x) = ax, find f -1(x) so y = ax then x = ay and now isolate y
• in order to isolate the y term, the logarithmic notation or symbol or function was invented or created so we write x = ay as y = loga(x)
Consider this approach here in column 1

evaluate log5(625) = x

5x = 625

5x = 54

x = 4

Now try log5(625) = x tis way:

log5(54) = x

log5(5)4 = x

Now I know from column 1 that the answer is 4 … so …

log5(5)4 = 4

4 x log5(5) = 4

4 x 1 = 4

(B) Properties of Logarithms- Logarithms of Powers
(B) Properties of Logarithms- Logarithms of Powers
• So if log5(625) = log5(5)4 = 4 x log5(5)
• It would suggest a rule of logarithms 
• logb(bx) = x
• Which we can generalize 
• logb(ax) = xlogb(a)
(C) Properties of Logarithms – Logs as Exponents
• Consider the example
• Recall that the expression log3(5) simply means “the exponent on 3 that gives 5”  let’s call that x
• So we are then asking you to place that same exponent (the x) on the same base of 3
• Therefore taking the exponent that gave us 5 on the base of 3 (x ) onto a 3 again, must give us the same 5!!!!
• We can demonstrate this algebraically as well
(C) Properties of Logarithms – Logs as Exponents
• Let’s take our exponential equation and write it in logarithmic form
• So becomes log3(x) = log3(5)
• Since both sides of our equation have a log3 then x = 5 as we had tried to reason out in the previous slide
• So we can generalize that
(D) Properties of Logarithms – Product Law
• Express logam + logan as a single logarithm
• We will let logam = x and logan = y
• So logam + logan becomes x + y
• But if logam = x, then ax = m and likewise ay = n
• Now take the product (m)(n) = (ax)(ay) = ax+y
• Rewrite mn=ax+y in log form  loga(mn)=x + y
• But x + y = logam + logan
• So thus loga(mn) = logam + logan
(E) Properties of Logarithms – Quotient Law
• We could develop a similar “proof” to the quotient law as we did with the product law  except we ask you to express logam - logan as a single logarithm
• As it turns out (or as is predictable), the simplification becomes as follows:
• loga(m/n) = loga(m) – loga(n)
(G) Examples
• (i) log354 + log3(3/2)
• (ii) log2144 - log29
• (iii) log30 + log(10/3)
• (iv) which has a greater value
• (a) log372 - log38 or (b) log500 + log2
• (v) express as a single value
• (a) 3log2x + 2log2y - 4log2a
• (b) log3(x+y) + log3(x-y) - (log3x + log3y)
• (vi) log2(4/3) - log2(24)
• (vii) (log25 + log225.6) - (log216 + log39)